Assessment of regional digital divide in Türkiye - Alp, Gülfiye Ozcan; Baycan, Tüzin (Quaestiones Geographicae, 2023)
Technological advancement has not been equally distributed. It has differed from country to country, region to region, and even among individuals. As a result, the digital divide has emerged as an umbrella term to represent these disparities. Recently, the research focus has shifted to the outcomes of information and communication technology usage or tangible benefits (the third-level digital divide). As an emerging economy, Türkiye must overcome the digital divide to maximise tangible benefits. Thus, this research starts by determining the digital divide indicators for Türkiye and goes further to examine the digital divide between regions in Türkiye. The main aim is to present a comprehensive index for the regional scale that is currently missing in the literature. To do so, this research starts with exploring the digital divide indicators. Then, with the help of principal component analysis (PCA), a new index is formulated for Türkiye. The result maps indicate digital inequalities both at regional and city scales, yet inequalities are more remarkable at the city scale. Increasing the diversity of technology usage, focusing on gender equality, expanding R&D expenditures, and supporting initiatives, especially ICT initiatives, will assist Türkiye in reducing digital inequalities.